O uso de ferramentas de gestão de qualidade nos processos da engenharia clínica - SOUZA, Ana Vitória Furtado de (2025)
With the growing technological advancements in the healthcare sector, effective management of medical equipment has become crucial to ensure the quality, efficiency, and safety of hospital services. This study addresses the relevance of applying quality management tools in Clinical Engineering, a subfield of Biomedical Engineering essential for the management and maintenance of medical equipment in healthcare settings. The increasing complexity of healthcare service providers and technological advancements demand effective approaches to ensure the quality, efficiency, and safety of hospital services. The central objective of this work is to understand how the use of these quality tools impacts the effectiveness of processes in Clinical Engineering. To achieve this, the adopted methodology involved a literature review, encompassing articles, books, and hospital accreditation manuals, as well as publications on quality management tools. Through this descriptive and qualitative approach, a comprehensive understanding of the impact of these tools on Clinical Engineering was sought. The results of this study confirm the effectiveness of quality management tools in optimizing processes, eliminating rework, improving financial management, and ensuring the safety of hospital service outcomes.